Influence factors on airborne pollen dispersal in a tropical island over China: morphology and meteorology - Mengyuan Pang; Ningyan Fu; Siyang Li (Atmospheric Environment: X)
Airborne pollen is an important primary biological aerosol particle in tropical regions, greatly impacting climate and human health. However, the pollen morphology in tropical areas, particularly their impact on pollen dispersal, remains unknown. To determine the relationship between the dispersal and morphology of airborne pollens, we collected the airborne pollen by Durham samplers at three vertical heights, including 1.5 m, ∼18.5 m, and ∼55 m in Haikou City, China. Pollen particles showed higher concentrations at higher heights above ground level. The quantitative analysis of single pollen particles based on the size index showed that the airborne pollen sizes in the tropics were mainly small (10–25 μm) (45.9%) and medium (25–50 μm) (32.2%). That's consistent with the pollen morphology of spring and summer flowering plants in the surrounding areas. The proportions of very small (<10 μm) and small (10–25 μm) pollen particles increased significantly with the vertical height. The shape index showed the prominent shape of airborne pollen was subspheroidal/spheroidal (∼80%). The pollen concentration of other shapes, like prolate or oblate, slightly increased with height. The Pearson correlation analysis showed that local meteorological conditions had an important role in influencing pollen amounts, with some associations found to be statistically significant. Temperature variables had significant positive correlation with pollen amounts, especially the maximum temperature (r = 0.71, P < 0.01). The rainfall and relative humidity exhibited a negative correlation with pollen concentration. Notably, pollen release was influenced by meteorological factors with a 1–7 day lagged effect. This study provided a near-ground vertical profile of tropical pollen concentration and morphology. These findings also offer a comprehensive understanding of how airborne pollen morphology and meteorological factors influence their transport and deposition characteristics on a tropical island.